Analisis Pengaruh Kompetensi Terhadap Kinerja Pegawai Satuan Polisi Pamong Praja Kota Pontianak - Parwidi, Parwidi; Muntaha, Muntaha (STIE Widya Manggala, 2020)
Competence is a behavior that more emphasis on productive behavior that must be owned and done by someone in carrying out an activity in order to excel outstanding. Performance of a person related to the level of success in doing something work in accordance with the field of duty in order to achieve organizational goals. Psychologically, a person’s abilities consist of the potential ability and the ability of reality. Therefore the Pontianak Municipal Police Prison Unit should be able to demonstrate its superiority through its competence in order to improve the performance of human resources. Thus expected employees can give the best contribution through the competence held for the achievement of good performance, so as to meet the target and the target work of individuals who are given and contribute to the success of achieving the target organization Pontianak City Pamong Praja Police Unit as a whole. The problem in this research is how the influence of competence to the performance of personnel of Police Unit of Pontianak Municipal Police?. Research Methods in the form of a survey, with a population of all employees at the Pontianak Municipal Police Service Unit of 110 people. Sampling using Census method. Data analysis using Multiple Linear Regression Multiple Linear Regression. The results of simultaneous research competence that includes knowledge, skills and individual behavior affect the performance. Partially knowledge and skills have an effect on to performance while individual behavior has no effect.